Karakterisasi Mutu Produk Kue Kering (Cookies) Hasil Substitusi Tepung Kepala Udang (Litopenaeus Vannamei) dan Tepung Terigu - Ishak, Ristionita; Sulistijowati, Rieny; Suherman, Sutianto Pratama (Transbahasa, 2023)
This research aimed to formulate and analyze organoleptic values and chemical parameters (moisture, protein, calcium contents) from cookies substituted with whiteleg shrimp head flour and wheat flour. The research employed the experimental method with two replications and three treatments, namely P1 (5 grams whiteleg shrimp head flour and 95 grams wheat flour), P2 (10 grams whiteleg shrimp head flour and 90 gram wheat flour), and P3 (15 grams whiteleg shrimp head flour and 85 grams wheat flour). Moreover, the parameters tested were organoleptic sharacteristics analyzed using Rasch model. The result analysis of the Rasch model in the treatment of coocies substituted with whiteleg shrimp head dlour and wheat flour produced organoleptic characteristic assessed by the panelists on 5 gr, 10 gr, and 15 gr levels, indicating that is was difficult for the panelists to asess color and aroma, while panelists easly assessed appearance, taste, and texture. The chemical parameters were analyzed using a completely randomized design and ANOVA (Analysis of Variance). The result of the ANOVA test depicted that different cookies treatments had a singnificant effect (P<0,05) on the content of cookies substituted with whiteleg shrimp head flour and wheat flour, so it continued whit Duncan’s Multiple Range Test. The value of Duncan’s multiple range test revealed a significant effect difference among each treatment, namely the water content at the 5 gr, 10 gr, and 15 gr levels signified that all treatments had no significant effect, the protein content indicated that 5 gr level was significantly different from the 10 gr level, and the 10 gr level was significanly different from the 15 gr level at the same time, the calcium content with levels of 5 gr, 10 gr and 15 gr indicated that all treatments were significantly different.